Analysis Hierarchy Process and Geospatial in Determination of the Alternative Locations for Temporary Disposal Site in Sumbersari District, Jember - Oktaviana, Rahma Harum; Dhokhikah, Yeny; Listyawati, Ratih Novi (Jurnal Wilayah dan Lingkungan, 2025)
Sumbersari District, one of the urban areas in Jember, meets the problems of a limited number of temporary disposal sites (TDS). The paper aims to determine an alternative location for a new temporary disposal site (TDS) in the Sumbersari District by combining the Analysis Hierarchy Process (AHP) and Geographic Information System (GIS) methods. The AHP method is applied to determine the priority land with predetermined variables and the GIS method is applied for weighting physical aspects and spatial to make decisions through buffering and overlay techniques. The results of the study show that AHP weighting obtains priority to land, namely areas that are dominated by land with ownership rights of the State, Property Rights, and Use Rights, land that has a distance of more than 1000 m from the existing TDS, and land that has existing TDS conditions with a storage capacity of more than 100 %. Meanwhile, based on the GIS method through buffering and overlay techniques on physical and priority land aspects, 10 alternative location points were obtained with a value of 26 (Quite feasible and priority). These points were then carried out by eld observations, resulting in 2 suitable locations, namely A1 in the Antirogo Village and K1 in the Kranjingan Village.